(untitled) (Bangladesh Journal of Pharmacology, 2015)
The study was tempted to explore the scientific basis for the medicinal use of Adiantum capillus-veneris L. in diarrhea using the in vivo and in vitro assays. The crude extract of dried leaves of A. capillus-veneris exhibited antidiarrheal effect against castor oil-induced diarrhea in mice at 300 and 500 mg/kg, similar to the effect loperamide. It was also found safe up to administered dose of 7 g/kg in mice. In isolated rabbit jejunum, extract of A. capillus-veneris showed a concentration-dependent relaxation of spontaneous and low K+ (25 mM)-induced contractions and had weak inhibitory effect on high K+ (80 mM), similar to the activity pattern of cromakalim, an ATP-dependent K+ channel opener. Interestingly, its inhibitory effect on spontaneous contractions was potentiated in the presence of atropine. These data demonstrates that A. capillus-veneris possesses antidiarrheal and antispasmodic properties mediated possibly through ATP-dependent K+ channels activation, thus providing scientific basis to its folk use in abdominal colic and diarrhea.